1993
DOI: 10.3109/00365529309098311
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in a Randomly Selected Population, Healthy Volunteers, and Patients with Gastric Ulcer and Gastric Adenocarcinoma: A Seroprevalence Study in Taiwan

Abstract: To investigate the association of Helicobacter pylori and gastric ulcer and adenocarcinoma, IgG antibodies against H. pylori were examined in 823 randomly selected subjects, 92 healthy volunteers, 117 patients with gastric ulcer, and 148 with gastric adenocarcinomas in Taiwan, where the prevalence of gastric adenocarcinoma is high. The seropositivity of this population in Taiwan was 54.4%. Gastric ulcer patients had a higher seropositivity (83.8%) than healthy volunteers (62.0%) and gastric adenocarcinoma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
6
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 25 publications
5
48
6
3
Order By: Relevance
“…So the in vivo prevalence of our biopsy-based study was lower than the seroprevalence of H. pylori infection. The age-specific seropositivity of H. pylori infection was higher in younger patients with duodenal and gastric ulcers in Taiwan (6)(7)(8). Because our younger subjects were not divided according to disease type, the incidence of H. pylori was lower in patients under 20 years in our study, as might be expected.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…So the in vivo prevalence of our biopsy-based study was lower than the seroprevalence of H. pylori infection. The age-specific seropositivity of H. pylori infection was higher in younger patients with duodenal and gastric ulcers in Taiwan (6)(7)(8). Because our younger subjects were not divided according to disease type, the incidence of H. pylori was lower in patients under 20 years in our study, as might be expected.…”
Section: Discussionsupporting
confidence: 62%
“…The lowest prevalence rates of H. pylori infection were seen in young patients aged below 20. Seroprevalence studies of H, pylori infection in Taiwan have reported that the overall seropositivity of H. pylori was highest in patients with duodenal and gastric ulcer (94.7%), duodenal ulcers (87.4%), and gastric ulcers (76.2%) (7,8). These rates were higher than the prevalence found in our biopsy-based investigation, and may reflect the fact that the previous studies detected both past and active H. pylori infection.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Fifteen years ago Lin et al reported the H. pylori seroprevalence of 62.0% among TW healthy volunteers, so it seems that situation is about the same now (16). The prevalence of atrophic gastritis of any degree and the more severe atrophy was not different among patients from different countries in our study.…”
Section: Fig 1 Distribution Of Different Degrees Of Atrophysupporting
confidence: 48%
“…Acredita-se que mais de um terço dos carcinomas gástri-cos seja atribuído à infecção pelo H. pylori. 26,33,73,100 Outras afecções associadas à infecção pelo H. pylori são linfoma de tecido linfóide associado à mucosa gástrica -MALToma, 105 dispepsia não-ulcerativa, 10,12 doenças coronarianas e cardiovasculares, 90,108,98,107 urticária idiopática crônica, 29,110,129 doenças auto-imunes (púrpura de Henoch-Shönlein, 77,111 trombocitopenia auto-imune, 43 síndrome de Sjögren 37 ) e enxaqueca. 42 Estudos sugerem que existe aumento na incidên-cia de refluxo gastroesofágico (RGE) após erradicação do H. pylori da mucosa gástrica.…”
Section: Introductionunclassified